THEORETICAL AND METHODOLOGICAL BASIS OF PHYSICAL DEVELOPMENT OF PRIMARY SCHOOL STUDENTS (Web of Teachers: Inderscience Research, 2025)
This article analyzes the theoretical and methodological foundations of the physical development of primary school students, in particular, the results of research conducted in the conditions of the Fergana region. The study tested the scientific works of foreign and domestic scientists, modern monitoring technologies, and methodological approaches based on Presidential decrees. According to the results, about 30% of primary school children have a low level of physical activity, which negatively affects their health and development. As a scientific novelty, methods of sensory monitoring and assessment of individual development have been successfully implemented in local conditions. The article serves to improve the quality of physical education from a scientific and practical point of view and to form an innovative methodological basis aimed at raising a healthy generation.